Immunomagnetic bead applied to immunodetection and preparation method thereof
By using carbon-coated iron nanoparticle plasma ammonization treatment and surface modification technology in immune magnetic beads, the problems of insufficient particle size uniformity and adsorption performance of existing magnetic beads are solved, and more efficient immune detection results are achieved .
Patent Information
- Application Number
- CN202411420463.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing immunomagnetic beads have shortcomings in particle size uniformity, surfactant functional group content and simplification of preparation methods, which affect their application effect in immune detection.
Carbon-coated iron nanoparticles were treated with plasma ammonization, amino carbon-coated iron nanoparticles were added, and the surface modification was made by silane coupling agent, combining immune ligand biological active substances and bovine serum protein to prepare high adsorption capacity Immune magnetic beads.
The size uniformity, stability and adsorption performance of the magnetic beads are improved, so that they show higher efficiency and sensitivity in immune detection, and the preparation method is simple and easy to perform.
Smart Images

Figure CN119178877A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of immunomagnetic bead preparation, and in particular to immunomagnetic bead used for immunoassay and a preparation method thereof. Background Art
[0002] Nanomagnetic beads are usually composed of a large number of magnetic nanoparticles fixed in a non-magnetic matrix, with a size range of tens of nanometers to hundreds of microns. The non-magnetic matrix is usually silica or an organic polymer. The smaller the particle size of the spherical particles, the larger the specific surface area (the ratio of surface area to volume), the more atoms on the surface of the particles, and the easier it is to combine with other atoms to form a stable structure, which has high chemical activity. The beads are usually dispersed in a liquid suspension, such as ethanol, isopropanol, sodium azide solution, and pure water. Magnetic beads in suspensions have become one of the most widely used nanomaterials in the fields of biology and chemistry due to their unique magnetism and interaction with external magnetic fields. Ferromagnetic materials have spontaneous magnetization and are also magnetic in the absence of an external magnetic field. Due to the small size effect of nanomaterials, ferromagnetic materials will exhibit superparamagnetism when the volume is below a certain critical value (iron oxide is usually less than 30nm). Superparamagnetism refers to the phenomenon that particles exhibit paramagnetism when the particle size is smaller than the critical size and the temperature is lower than the Curie temperature and higher than the transition temperature. When an external magnetic field is applied, it will be magnetized and exhibit magnetism, and the magnetic susceptibility is much higher than that of ordinary paramagnets. Superparamagnetic particles only exhibit magnetism when an external magnetic field is present, which gives them unique advantages in their application in the biological environment. The superparamagnetism of magnetic nanoparticles greatly facilitates the separation, enrichment and purification of samples, and has also received widespread attention in immunoassays.
[0003] As a spherical composite material with a diameter of nanometers to micrometers, magnetic beads can achieve efficient separation of target substances under the action of an external magnetic field; and by modifying recognition molecules such as antibodies on magnetic beads and utilizing specific immunological reactions, they can be used to efficiently and specifically bind to corresponding antigens / antibodies, thereby forming immune complexes. Under the action of an external magnetic field, immune complexes can be efficiently separated from other substances, thereby achieving the purpose of positive or negative selection of specific targets. Since immunomagnetic beads have the advantages of fast separation speed, high efficiency, and simple operation, they are extremely widely used in the fields of immunoassay, cell separation, biomacromolecule purification, and molecular biology. .
[0004] However, the particle size uniformity, surface active functional group content, stability and simplification of the preparation method of the existing immunomagnetic beads still need to be improved. Therefore, an immunomagnetic bead for use in immune detection and a preparation method thereof are proposed. Summary of the invention
[0005] The present invention aims to provide an immunomagnetic bead for use in immunoassay and a method for preparing the same. The method has a simple preparation process and the prepared immunomagnetic beads have good uniformity and stability.
[0006] To achieve the above object, the present invention provides a method for preparing immunomagnetic beads for immunoassay, comprising the following steps:
[0007] S1: Preparation of carbon-coated iron nanoparticles;
[0008] S2: the carbon-coated iron nanoparticles are subjected to plasma ammoniation treatment to obtain amino-carbon-coated iron nanoparticles;
[0009] S3: washing the amino carbon-coated iron nanoparticles with deionized water for 1-2 times, adjusting the pH of the ethanol aqueous solution to 4.5-5.5, adding the washed amino carbon-coated iron nanoparticles, adding a silane coupling agent to modify the surface thereof, reacting at room temperature for 12-24 hours, then placing in a first buffer solution, adding an immune ligand bioactive substance, stirring and incubating, washing with a second buffer solution for 3-4 times by magnetic separation, adding bovine serum albumin, mixing and reacting at 4°C overnight, blocking the magnetic beads, and obtaining immune magnetic beads;
[0010] S4: The immunomagnetic beads were washed three times with pure water, dissolved in a phosphate buffer solution with a pH of 7.0-7.4, and stored at 4°C for later use.
[0011] Preferably, the steps for preparing the carbon-coated iron nanoparticles are:
[0012] S21: taking sucrose and ferric nitrate in a certain mass ratio, adding the sucrose and sodium dodecylbenzene sulfonate (1% by mass of sucrose) into an ethanol aqueous solution to fully dissolve them to obtain a sucrose solution, adding a hydrazine hydrate solution having a mass concentration of 82% into the sucrose solution, and adjusting the solution to a pH of 10 with concentrated ammonia water to obtain a mixed solution A, wherein the added volume of the hydrazine hydrate solution is 80%-120% of the volume of the sucrose solution;
[0013] S22: dissolving ferric nitrate and an equal amount of sodium dodecylbenzene sulfonate as in step S21 in anhydrous ethanol to obtain a mixed solution B;
[0014] S23: Solution B is added dropwise to the mixed solution A at a rate of 50-90 drops / min, and physical stirring and ultrasonic stirring are maintained during the dropping process. After the dropping is completed, a mixed solution C is obtained, and the mixed solution C is placed in an oven and dried at 80°C to obtain a precursor. The precursor is carbonized at 550°C for 2h under a nitrogen atmosphere, and then the temperature is increased to 1000°C, annealed for 7h, cooled to room temperature, and then ground to obtain the carbon-coated iron nanoparticles.
[0015] Preferably, the preparation steps of the amino carbon-coated iron nanoparticles are:
[0016] S31: Add the carbon-coated iron nanoparticles into a microwave plasma device, use a 2.45 GHz microwave source to excite plasma, introduce ammonia and nitrogen, and excite NH 3 、N 2 Plasma, microwave power of 1.5-3kW, ratio of ammonia to nitrogen of 1-3:1, total gas flow rate of ammonia and nitrogen of 100-150sccm, reaction temperature of 200-400°C, reaction time of 3-5h to obtain aminocarbon-coated iron nanoparticles;
[0017] S32: After the reaction is completed, turn off the microwave power supply, continue to introduce ammonia and nitrogen into the system and cool it to room temperature at a rate of 5-15°C / min, turn off the ammonia and nitrogen system, and take out the aminocarbon-coated iron nanoparticles.
[0018] Preferably, in step S21, the mass ratio of sucrose to ferric nitrate is 5:1.
[0019] Preferably, in step S3, the first buffer solution is 0.1M PBS containing 0.05% Tween-20, pH 7.0-7.4, and the second buffer solution is 0.1M PBS, 0.1% BSA, and 0.05% Tween-20.
[0020] Preferably, the silane coupling agent in step S3 is any one of 3-glycidylpropyltrimethoxysilane, aminopropyltriethoxysilane and aminopropyltrimethoxysilane.
[0021] Preferably, the immune ligand in step S3 is one of the following substances: enzyme, antibody, antigen, DNA, RNA.
[0022] The present invention also provides an immunomagnetic bead, wherein the immunomagnetic bead structure comprises amino carbon-coated iron nanoparticles and an immune ligand coupled to the outside of the amino carbon-coated iron nanoparticles.
[0023] The beneficial effects of the present invention are as follows: the present invention successfully prepares carbon-coated metallic iron nanoparticles by using sucrose as a carbon source and ferric nitrate as a metal source through a liquid phase reduction-high temperature annealing method, and uses a plasma method to excite NH 3 、N 2 Plasma allows carbon-coated metallic iron nanoparticles to connect to nitrogen-containing groups such as amino groups. Functional groups such as amino groups can provide lone pairs of electrons, making the surface of the magnetic beads have a certain electrophilicity, thereby interacting with some positively charged molecules through van der Waals forces, effectively improving the adsorption capacity of the magnetic beads. The preparation method of the entire immunomagnetic beads is simple, and the particle size can be designed by adjusting the reaction parameters of the carbon-coated iron nanoparticles to achieve the purpose of controlling the size. The immunomagnetic beads proposed by the present invention have stable size uniformity, good adsorption performance, and are simple to store and easy to use. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of protein adsorption on immunomagnetic beads.
[0025] Figure 2 Schematic diagram of protein elution from immunomagnetic beads. DETAILED DESCRIPTION
[0026] The embodiments described below are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The present invention provides a method for preparing immunomagnetic beads for use in immunoassay, comprising the following steps:
[0028] S1: Preparation of carbon-coated iron nanoparticles;
[0029] S2: the carbon-coated iron nanoparticles are subjected to plasma ammoniation treatment to obtain amino-carbon-coated iron nanoparticles;
[0030] S3: washing the amino carbon-coated iron nanoparticles with deionized water for 1-2 times, adjusting the pH of the ethanol aqueous solution to 4.5-5.5, adding the washed amino carbon-coated iron nanoparticles, adding a silane coupling agent to modify the surface thereof, reacting at room temperature for 12-24 hours, then placing in a first buffer solution, adding an immune ligand bioactive substance, stirring and incubating, washing with a second buffer solution for 3-4 times by magnetic separation, adding bovine serum albumin, mixing and reacting at 4°C overnight, blocking the magnetic beads, and obtaining immune magnetic beads;
[0031] S4: The immunomagnetic beads were washed three times with pure water, dissolved in a phosphate buffer solution with a pH of 7.0-7.4, and stored at 4°C for later use.
[0032] The preparation steps of the carbon-coated iron nanoparticles are:
[0033] S21: taking sucrose and ferric nitrate in a certain mass ratio, adding the sucrose and sodium dodecylbenzene sulfonate (1% by mass of sucrose) into an ethanol aqueous solution to fully dissolve them to obtain a sucrose solution, adding a hydrazine hydrate solution having a mass concentration of 82% into the sucrose solution, and adjusting the solution to a pH of 10 with concentrated ammonia water to obtain a mixed solution A, wherein the added volume of the hydrazine hydrate solution is 80%-120% of the volume of the sucrose solution;
[0034] S22: dissolving ferric nitrate and an equal amount of sodium dodecylbenzene sulfonate as in step S21 in anhydrous ethanol to obtain a mixed solution B;
[0035] S23: Solution B is added dropwise to the mixed solution A at a rate of 50-90 drops / min, and physical stirring and ultrasonic stirring are maintained during the dropping process. After the dropping is completed, a mixed solution C is obtained, and the mixed solution C is placed in an oven and dried at 80°C to obtain a precursor. The precursor is carbonized at 550°C for 2h under a nitrogen atmosphere, and then the temperature is increased to 1000°C, annealed for 7h, cooled to room temperature, and then ground to obtain the carbon-coated iron nanoparticles.
[0036] The preparation steps of the amino carbon-coated iron nanoparticles are as follows:
[0037] S31: Add the carbon-coated iron nanoparticles into a microwave plasma device, use a 2.45 GHz microwave source to excite plasma, introduce ammonia and nitrogen, and excite NH 3 、N 2 Plasma, microwave power of 1.5-3kW, ratio of ammonia to nitrogen of 1-3:1, total gas flow rate of ammonia and nitrogen of 100-150sccm, reaction temperature of 200-400°C, reaction time of 3-5h to obtain aminocarbon-coated iron nanoparticles;
[0038] S32: After the reaction is completed, turn off the microwave power supply, continue to introduce ammonia and nitrogen into the system and cool it to room temperature at a rate of 5-15°C / min, turn off the ammonia and nitrogen system, and take out the aminocarbon-coated iron nanoparticles.
[0039] Wherein, the mass ratio of sucrose to ferric nitrate in step S21 is 5:1.
[0040] In step S3, the first buffer solution is 0.1M PBS containing 0.05% Tween-20, pH 7.0-7.4, and the second buffer solution is 0.1M PBS, 0.1% BSA, and 0.05% Tween-20.
[0041] In step S3, the silane coupling agent is any one of 3-glycidylpropyltrimethoxysilane, aminopropyltriethoxysilane and aminopropyltrimethoxysilane.
[0042] In step S3, the immune ligand is one of the following substances: enzyme, antibody, antigen, DNA, RNA.
[0043] The present invention also provides an immunomagnetic bead, wherein the immunomagnetic bead structure comprises amino carbon-coated iron nanoparticles and an immune ligand coupled to the outside of the amino carbon-coated iron nanoparticles.
[0044] Example 1
[0045] This embodiment provides an immunomagnetic bead, and the preparation steps of the immunomagnetic bead are as follows:
[0046] S1: Preparation of carbon-coated iron nanoparticles: sucrose and ferric nitrate are taken in a mass ratio of 5:1, and the sucrose and sodium dodecylbenzene sulfonate (1% by mass of the sucrose) are added to an ethanol aqueous solution to fully dissolve to obtain a sucrose solution, and a hydrazine hydrate solution with a mass concentration of 82% is added to the sucrose solution, and the solution is adjusted to a pH of 10 with concentrated ammonia water to obtain a mixed solution A, wherein the added volume of the hydrazine hydrate solution is 80% of the volume of the sucrose solution; ferric nitrate and an equal amount of the sodium dodecylbenzene sulfonate are fully dissolved in anhydrous ethanol to obtain a mixed solution B, and solution B is added dropwise to the mixed solution A at a rate of 60 drops / min, and physical stirring and ultrasonic stirring are maintained during the dropping process, and a mixed solution C is obtained after the dropping is completed, and the mixed solution C is placed in an oven and dried at 80°C to obtain a precursor, and the precursor is carbonized at 550°C for 2h under a nitrogen atmosphere, and then the temperature is increased to 1000°C, annealed for 7h, cooled to room temperature, and then ground to obtain the carbon-coated iron nanoparticles;
[0047] S2: Preparation of amino carbon-coated iron nanoparticles: Add the carbon-coated iron nanoparticles into a microwave plasma device, use a 2.45 GHz microwave source to excite plasma, introduce ammonia and nitrogen, and excite NH 3 、N 2 Plasma, microwave power of 2.5kW, ratio of ammonia to nitrogen of 3:1, total gas flow rate of ammonia and nitrogen of 150sccm, reaction temperature of 200°C, reaction for 4h to obtain amino-carbon-coated iron nanoparticles, after the reaction is completed, microwave power is turned off, ammonia and nitrogen are continuously introduced into the system and cooled to room temperature at a rate of 10°C / min, ammonia and nitrogen are turned off, and the amino-carbon-coated iron nanoparticles are taken out;
[0048] S3: Wash 5 mg of the amino carbon-coated iron nanoparticles with deionized water twice, adjust the pH of 10 mL of ethanol aqueous solution (ethanol: water is 95:5) to 5.5, add the washed amino carbon-coated iron nanoparticles, add 0.1 mL of aminopropyltriethoxysilane to modify its surface, react at room temperature for 18 hours, then place in the first buffer solution, add 1 mL of immunoglobulin G antibody (1 mg / mL), stir and incubate, wash with the second buffer solution magnetic separation 3 times, add 5 mL of bovine serum albumin (1 mg / mL), mix and react overnight at 4°C, block the magnetic beads, and obtain immunomagnetic beads;
[0049] S4: The immunomagnetic beads were washed three times with pure water, dissolved in a phosphate buffer solution with a pH of 7.0, and stored at 4°C for later use.
[0050] Example 2
[0051] This embodiment provides an immunomagnetic bead, and the preparation steps of the immunomagnetic bead are as follows:
[0052] S1: Preparation of carbon-coated iron nanoparticles: sucrose and ferric nitrate are taken in a mass ratio of 5:1, and the sucrose and sodium dodecylbenzene sulfonate (1% by mass of the sucrose) are added to an ethanol aqueous solution to fully dissolve to obtain a sucrose solution, and a hydrazine hydrate solution with a mass concentration of 82% is added to the sucrose solution, and the solution is adjusted to a pH of 10 with concentrated ammonia water to obtain a mixed solution A, wherein the added volume of the hydrazine hydrate solution is 100% of the volume of the sucrose solution; ferric nitrate and an equal amount of the sodium dodecylbenzene sulfonate are fully dissolved in anhydrous ethanol to obtain a mixed solution B, and solution B is added dropwise to the mixed solution A at a rate of 80 drops / min, and physical stirring and ultrasonic stirring are maintained during the dropping process, and a mixed solution C is obtained after the dropping is completed, and the mixed solution C is placed in an oven and dried at 80°C to obtain a precursor, and the precursor is carbonized at 550°C for 2h under a nitrogen atmosphere, and then the temperature is increased to 1000°C, annealed for 7h, cooled to room temperature, and then ground to obtain the carbon-coated iron nanoparticles;
[0053] S2: Preparation of amino carbon-coated iron nanoparticles: Add the carbon-coated iron nanoparticles into a microwave plasma device, use a 2.45 GHz microwave source to excite plasma, introduce ammonia and nitrogen, and excite NH 3 、N 2 Plasma, microwave power of 2.5kW, ratio of ammonia to nitrogen of 3:1, total gas flow rate of ammonia and nitrogen of 120sccm, reaction temperature of 250°C, reaction for 4h to obtain amino-carbon-coated iron nanoparticles, after the reaction is completed, microwave power is turned off, ammonia and nitrogen are continued to be introduced into the system, cooled to room temperature at a rate of 10°C / min, ammonia and nitrogen systems are turned off, and the amino-carbon-coated iron nanoparticles are taken out;
[0054] S3: Wash 5 mg of the amino carbon-coated iron nanoparticles with deionized water twice, adjust the pH of 10 mL of ethanol aqueous solution (ethanol: water is 95:5) to 5.5, add the washed amino carbon-coated iron nanoparticles, add 0.1 mL of aminopropyltriethoxysilane to modify its surface, react at room temperature for 18 hours, then place in the first buffer solution, add 1 mL of immunoglobulin G antibody (1 mg / mL), stir and incubate, wash with the second buffer solution magnetic separation 3 times, add 5 mL of bovine serum albumin (1 mg / mL), mix and react overnight at 4°C, block the magnetic beads, and obtain immunomagnetic beads;
[0055] S4: The immunomagnetic beads were washed three times with pure water, dissolved in a phosphate buffer solution with a pH of 7.0, and stored at 4°C for later use.
[0056] Example 3
[0057] This embodiment provides an immunomagnetic bead, and the preparation steps of the immunomagnetic bead are as follows:
[0058] S1: Preparation of carbon-coated iron nanoparticles: sucrose and ferric nitrate are taken in a mass ratio of 5:1, and the sucrose and sodium dodecylbenzene sulfonate (1% by mass of the sucrose) are added to an ethanol aqueous solution to fully dissolve to obtain a sucrose solution, and a hydrazine hydrate solution with a mass concentration of 82% is added to the sucrose solution, and the solution is adjusted to a pH of 10 with concentrated ammonia water to obtain a mixed solution A, wherein the added volume of the hydrazine hydrate solution is 80% of the volume of the sucrose solution; ferric nitrate and an equal amount of the sodium dodecylbenzene sulfonate are fully dissolved in anhydrous ethanol to obtain a mixed solution B, and solution B is added dropwise to the mixed solution A at a rate of 60 drops / min, and physical stirring and ultrasonic stirring are maintained during the dropping process, and a mixed solution C is obtained after the dropping is completed, and the mixed solution C is placed in an oven and dried at 80°C to obtain a precursor, and the precursor is carbonized at 550°C for 2h under a nitrogen atmosphere, and then the temperature is increased to 1000°C, annealed for 7h, cooled to room temperature, and then ground to obtain the carbon-coated iron nanoparticles;
[0059] S2: Preparation of amino carbon-coated iron nanoparticles: Add the carbon-coated iron nanoparticles into a microwave plasma device, use a 2.45 GHz microwave source to excite plasma, introduce ammonia and nitrogen, and excite NH 3 、N 2 Plasma, microwave power of 2.5kW, ratio of ammonia to nitrogen of 2:1, total gas flow rate of ammonia and nitrogen of 150sccm, reaction temperature of 300°C, reaction for 5h to obtain amino-carbon-coated iron nanoparticles, after the reaction is completed, microwave power is turned off, ammonia and nitrogen are continuously introduced into the system and cooled to room temperature at a rate of 10°C / min, ammonia and nitrogen are turned off, and the amino-carbon-coated iron nanoparticles are taken out;
[0060] S3: Wash 5 mg of the amino carbon-coated iron nanoparticles with deionized water twice, adjust the pH of 10 mL of ethanol aqueous solution (ethanol: water is 95:5) to 5.5, add the washed amino carbon-coated iron nanoparticles, add 0.1 mL of aminopropyltriethoxysilane to modify its surface, react at room temperature for 18 hours, then place in the first buffer solution, add 1 mL of immunoglobulin G antibody (1 mg / mL), stir and incubate, wash with the second buffer solution magnetic separation 3 times, add 5 mL of bovine serum albumin (1 mg / mL), mix and react overnight at 4°C, block the magnetic beads, and obtain immunomagnetic beads;
[0061] S4: The immunomagnetic beads were washed three times with pure water, dissolved in a phosphate buffer solution with a pH of 7.0, and stored at 4°C for later use.
[0062] Example 4
[0063] This embodiment provides an immunomagnetic bead, and the preparation steps of the immunomagnetic bead are as follows:
[0064] S1: Preparation of carbon-coated iron nanoparticles: sucrose and ferric nitrate are taken in a mass ratio of 2:1, and the sucrose and sodium dodecylbenzene sulfonate with a mass percentage of 1% of the sucrose are added to an ethanol aqueous solution to fully dissolve to obtain a sucrose solution, and a hydrazine hydrate solution with a mass concentration of 82% is added to the sucrose solution, and the solution is adjusted to a pH of 10 with concentrated ammonia water to obtain a mixed solution A, wherein the added volume of the hydrazine hydrate solution is 80% of the volume of the sucrose solution; ferric nitrate and an equal amount of the sodium dodecylbenzene sulfonate are fully dissolved in anhydrous ethanol to obtain a mixed solution B, and solution B is added dropwise to the mixed solution A at a rate of 60 drops / min, and physical stirring and ultrasonic stirring are maintained during the dropping process, and a mixed solution C is obtained after the dropping is completed, and the mixed solution C is placed in an oven and dried at 80°C to obtain a precursor, and the precursor is carbonized at 550°C for 2h under a nitrogen atmosphere, and then the temperature is increased to 1000°C, annealed for 7h, cooled to room temperature, and then ground to obtain the carbon-coated iron nanoparticles;
[0065] S2: Preparation of amino carbon-coated iron nanoparticles: Add the carbon-coated iron nanoparticles into a microwave plasma device, use a 2.45 GHz microwave source to excite plasma, introduce ammonia and nitrogen, and excite NH 3 、N 2 Plasma, microwave power of 2.5kW, ratio of ammonia to nitrogen of 3:1, total gas flow rate of ammonia and nitrogen of 150sccm, reaction temperature of 200°C, reaction for 4h to obtain amino-carbon-coated iron nanoparticles, after the reaction is completed, microwave power is turned off, ammonia and nitrogen are continuously introduced into the system and cooled to room temperature at a rate of 10°C / min, ammonia and nitrogen are turned off, and the amino-carbon-coated iron nanoparticles are taken out;
[0066] S3: Wash 5 mg of the amino carbon-coated iron nanoparticles with deionized water twice, adjust the pH of 10 mL of ethanol aqueous solution (ethanol: water is 95:5) to 5.5, add the washed amino carbon-coated iron nanoparticles, add 0.1 mL of aminopropyltriethoxysilane to modify its surface, react at room temperature for 18 hours, then place in the first buffer solution, add 1 mL of immunoglobulin G antibody (1 mg / mL), stir and incubate, wash with the second buffer solution magnetic separation 3 times, add 5 mL of bovine serum albumin (1 mg / mL), mix and react overnight at 4°C, block the magnetic beads, and obtain immunomagnetic beads;
[0067] S4: The immunomagnetic beads were washed three times with pure water, dissolved in a phosphate buffer solution with a pH of 7.0, and stored at 4°C for later use.
[0068] Example 5
[0069] This embodiment provides an immunomagnetic bead, and the preparation steps of the immunomagnetic bead are as follows:
[0070] S1: Preparation of carbon-coated iron nanoparticles: sucrose and ferric nitrate are taken in a mass ratio of 5:1, and the sucrose and sodium dodecylbenzene sulfonate (1% by mass of the sucrose) are added to an ethanol aqueous solution to fully dissolve to obtain a sucrose solution, and a hydrazine hydrate solution with a mass concentration of 82% is added to the sucrose solution, and the solution is adjusted to a pH of 10 with concentrated ammonia water to obtain a mixed solution A, wherein the added volume of the hydrazine hydrate solution is 80% of the volume of the sucrose solution; ferric nitrate and an equal amount of the sodium dodecylbenzene sulfonate are fully dissolved in anhydrous ethanol to obtain a mixed solution B, and solution B is added dropwise to the mixed solution A at a rate of 60 drops / min, and physical stirring and ultrasonic stirring are maintained during the dropping process, and a mixed solution C is obtained after the dropping is completed, and the mixed solution C is placed in an oven and dried at 80°C to obtain a precursor, and the precursor is carbonized at 550°C for 2h under a nitrogen atmosphere, and then the temperature is increased to 1000°C, annealed for 7h, cooled to room temperature, and then ground to obtain the carbon-coated iron nanoparticles;
[0071] S2: 5 mg of the carbon-coated iron nanoparticles were washed twice with deionized water, the pH of 10 mL of ethanol aqueous solution (ethanol: water is 95:5) was adjusted to 5.5, the washed carbon-coated iron nanoparticles were added, 0.1 mL of aminopropyltriethoxysilane was added to modify the surface, the mixture was reacted at room temperature for 18 h, and then placed in a first buffer solution, 1 mL of immunoglobulin G antibody (1 mg / mL) was added, the mixture was stirred and incubated, the mixture was washed 3 times with a second buffer solution, 5 mL of bovine serum albumin (1 mg / mL) was added, the mixture was mixed and reacted overnight at 4°C, and the magnetic beads were blocked to obtain immunomagnetic beads;
[0072] S3: The immunomagnetic beads were washed three times with pure water, dissolved in a phosphate buffer solution with a pH of 7.0, and stored at 4°C for later use.
[0073] In the above embodiment, the first buffer solution is 0.1M PBS containing 0.05% Tween-20, pH 7.0-7.4, and the second buffer solution is 0.1M PBS, 0.1% BSA, and 0.05% Tween-20.
[0074] The adsorption capacity of the immunomagnetic beads proposed in Examples 1-5 was compared, and the test method was as follows:
[0075] Immunoglobulin G antibody was added to Examples 1 to 5, and the washing solution was collected after stirring and incubating. After precipitation, the supernatant was aspirated, and the amount of unadsorbed protein was detected according to the instructions of the BCA protein quantification kit. The amount of protein adsorbed by the magnetic beads was calculated according to formula (1). The magnetic beads were washed with pure water, and the binding tightness of the protein on the magnetic beads was detected.
[0076] Adsorbed protein amount = total protein amount - unadsorbed protein amount (1)
[0077] The protein adsorption capacity of the immunomagnetic beads of Examples 1-5 is shown in Figure 1 .
[0078] Then, the immunomagnetic beads of Example 1-5 were eluted and the amount of eluted protein was measured. Figure 2 .
[0079] from Figure 1 and Figure 2 It can be seen that the magnetic beads proposed in the present invention have a higher adsorption capacity, while the sucrose ratio used in Example 4 is reduced, and the coating rate is affected, which will have a greater impact on the subsequent adsorption capacity of the magnetic beads. In Example 5, the carbon-coated iron nanoparticles were not subjected to plasma ammoniation treatment, and the protein adsorption capacity of the obtained magnetic beads was far inferior to that of the magnetic beads prepared in Examples 1-3, indicating that connecting nitrogen-containing groups such as amino groups on the surface of the magnetic beads is beneficial to improving the adsorption capacity of the magnetic beads. Figure 2 It can be seen that the magnetic beads proposed in Examples 1-3 adsorb proteins more firmly and are not easy to elute. Improving the adsorption of magnetic beads is of great significance for improving the stability of magnetic beads and detection sensitivity.
[0080] The present invention is described in detail above in conjunction with the embodiments. It should be noted that the various specific technical features described in the above specific embodiments can be combined and changed in any suitable manner without contradiction, and the present invention will not further describe various possible combinations. In addition, other variations and combinations of the various technical features of the present invention should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing immunomagnetic beads for use in immune detection, characterized in that: The steps include: S1: Preparation of carbon-coated iron nanoparticles; S2: the carbon-coated iron nanoparticles are subjected to plasma ammoniation treatment to obtain amino-carbon-coated iron nanoparticles; S3: washing the amino carbon-coated iron nanoparticles with deionized water for 1-2 times, adjusting the pH of the ethanol aqueous solution to 4.5-5.5, adding the washed amino carbon-coated iron nanoparticles, adding a silane coupling agent to modify the surface thereof, reacting at room temperature for 12-24 hours, then placing in a first buffer solution, adding an immune ligand bioactive substance, stirring and incubating, washing with a second buffer solution for 3-4 times by magnetic separation, adding bovine serum albumin, mixing and reacting at 4°C overnight, blocking the magnetic beads, and obtaining immune magnetic beads; S4: The immunomagnetic beads were washed three times with pure water, dissolved in a phosphate buffer solution with a pH of 7.0-7.4, and stored at 4°C for later use.
2. The method for preparing immunomagnetic beads for immunoassay according to claim 1, characterized in that: The preparation steps of the carbon-coated iron nanoparticles are: S21: taking sucrose and ferric nitrate in a certain mass ratio, adding the sucrose and sodium dodecylbenzene sulfonate (1% by mass of sucrose) into an ethanol aqueous solution to fully dissolve them to obtain a sucrose solution, adding a hydrazine hydrate solution having a mass concentration of 82% into the sucrose solution, and adjusting the solution to a pH of 10 with concentrated ammonia water to obtain a mixed solution A, wherein the added volume of the hydrazine hydrate solution is 80%-120% of the volume of the sucrose solution; S22: dissolving ferric nitrate and an equal amount of sodium dodecylbenzene sulfonate as in step S21 in anhydrous ethanol to obtain a mixed solution B; S23: Solution B is added dropwise to the mixed solution A at a rate of 50-90 drops / min, and physical stirring and ultrasonic stirring are maintained during the dropping process. After the dropping is completed, a mixed solution C is obtained, and the mixed solution C is placed in an oven and dried at 80°C to obtain a precursor. The precursor is carbonized at 550°C for 2h under a nitrogen atmosphere, and then the temperature is increased to 1000°C, annealed for 7h, cooled to room temperature, and then ground to obtain the carbon-coated iron nanoparticles.
3. The method for preparing immunomagnetic beads for immunoassay according to claim 2, characterized in that: The preparation steps of the amino carbon-coated iron nanoparticles are as follows: S31: adding the carbon-coated iron nanoparticles into a microwave plasma device, using a 2.45 GHZ microwave source to excite plasma, introducing ammonia and nitrogen, exciting NH3 and N2 plasma, the microwave power is 1.5-3 kW, the ratio of ammonia to nitrogen is 1-3:1, the total gas flow rate of ammonia and nitrogen is 100-150 sccm, the reaction temperature is 200-400° C., and the reaction is carried out for 3-5 hours to obtain amino-carbon-coated iron nanoparticles; S32: After the reaction is completed, turn off the microwave power supply, continue to introduce ammonia and nitrogen into the system and cool it to room temperature at a rate of 5-15°C / min, turn off the ammonia and nitrogen system, and take out the aminocarbon-coated iron nanoparticles.
4. The method for preparing immunomagnetic beads for immunoassay according to claim 2, characterized in that: The mass ratio of sucrose to ferric nitrate in step S21 is 5:
1.
5. The method for preparing immunomagnetic beads for immunoassay according to claim 1, characterized in that: In step S3, the first buffer solution is 0.1M PBS containing 0.05% Tween-20, pH 7.0-7.4, and the second buffer solution is 0.1M PBS, 0.1% BSA, and 0.05% Tween-20.
6. The method for preparing immunomagnetic beads for immunoassay according to claim 1, characterized in that: In step S3, the silane coupling agent is any one of 3-glycidylpropyltrimethoxysilane, aminopropyltriethoxysilane and aminopropyltrimethoxysilane.
7. The method for preparing immunomagnetic beads for immunoassay according to claim 5, characterized in that: In step S3, the immune ligand is one of the following substances: enzyme, antibody, antigen, DNA, RNA.
8. An immunomagnetic bead prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The immunomagnetic bead structure comprises amino carbon-coated iron nanoparticles and immune ligands coupled to the outside of the amino carbon-coated iron nanoparticles.
Citation Information
Patent Citations
Inorganic material surface biological method
CN101214395A
Method for preparing boron-doped diamond film electrode for detecting dopamine
CN102520042A
Immunomagnetic beads applied to immunodetection and preparation method of immunomagnetic beads
CN105467112A
Preparation method of carbon-coated iron nanocatalyst
CN106732598A
Preparation and purification method of plasma ammoniation graphene and magnetic core structure nanoparticles
CN116143110A
